The posterior surgical treatment and outcomes of cervical spondylotic myelopathy: Why not C5 nerve root palsy occur (Annals of Medical Research, 2021)
Aim: Cervical spondylotic myelopathy is an age-related degenerative spinal pathology. Anterior or posterior approaches are preferredfor surgical treatment. C5 palsy is a common complication after the posterior approach. The aim of our study is to describe themodified laminectomy technique, evaluate short-time surgical outcomes and comment on the C5 nerve root palsy formation.Materials and Methods: 83 patients who had been treated by modified laminectomy for cervical spondylotic myelopathy between theyears 2012 and 2017 in our clinic were undertaken in our study. We evaluated the preoperative and postoperative neurologic statusof the patients with VAS and JOA scales, complications (C5 palsy) of surgical treatment. The posterior approach was not performedat patients with a >13 degree angle of cervical curvature.Results: 61 of 83 patients were male and 22 were female. The mean age at the time of surgery was 57.8±8.3. The average JOA scalescore was 9.4±0.9 preoperatively, 10.1±.0.9 early postoperatively and 15.1±1.0 during the late postoperative follow-up. The averageangle of the cervical curvature preoperatively-postoperatively was 17.1±2.6 and 15.8±2.4 respectively. There weren’t any symptomsfor C5 nerve root palsy which is a common postoperative complication.Conclusions: The cervical posterior laminectomy, which includes en-bloc laminectomy and preserving of the facet joint capsule,allows a sufficient and safe decompression of the neural structures for cervical spondylotic myelopathy.